Evolutionary echoes of emotion: Humans mimic other primate expressions - Ursula Hess; Till Kastendieck; M. Gizem Erkol; Heidi Mauersberger; Marina Davila-Ross; Katja Liebal; Elisabetta Palagi (PLoS ONE, 2026)
Humans readily mimic the emotional behavior of conspecifics -- a behavior linked to empathy. Yet, whether humans unconsciously mimic the emotional expressions of non-human primates remains an open question. Human observers watched short videos with positive (play-face), negative (open-mouth threat display) or neutral expressions by monkeys and apes (while their own facial expressions were filmed and automatically coded), rated the expressions for emotional content and indicated their degree of liking of and closeness to the primates. Participants mimicked both positive and negative expressions and were able to correctly identify the expressions as positive or negative. These findings shed new light on the deep-rooted, cross-species nature of emotional connection, suggesting that humans are able to empathize and mirror the emotions of other species.